TinyTorrent: Combining BitTorrent and SensorNets - Holger Fritsche, Karsten (Trinity College Dublin. Department of Computer Science, 2005)
The first of the two goals of this research was to investigate the BitTorrent protocol to determine what features make it successful on an Internet scale. These features include its ability to rapidly replicate data across the network, while ensuring fair participation of peers in the network. This resulted in the design and development of the TinyTorrent protocol, which adapted these BitTorrent features for a SensorNet environment. TinyTorrent was implemented for the Crossbow MICA2 hardware platform using nesC. The second goal was to explore a means of exposing SensorNet data to external systems. This resulted in the development of a SensorNet Plugin for the Azureus BitTorrent client, based on a proxy architecture. The SensorNet Plugin enables SensorNets to publish data to the BitTorrent network, and also acts as a tracker for the SensorNet running TinyTorrent. The TinyTorrent system was evaluated by experiment and simulation to determine the protocol overhead, energy consumption characteristics, effects of interference and real-world throughput. The evaluation showed that the use of more complex algorithms is feasible provided these lead to a reduction in the number or size of messages.
Keywords: Computer Science